Managing and Organizations : An Introduction to Theory and Practice - Clegg, Stewart R. (SAGE Publications, Ltd. (UK), 2021)
Covering all the basics in organizational behaviour, as well critically reflecting on the institutions and practices of business life, the sixth edition of Managing and Organizations: An Introduction to Theory and Practice has been updated to include: ·        Cutting-edge content on diversity and inclusion, design thinking, followership and deglobalization ·        New and updated ′In Practice′ boxes offering real-world examples ·        Engaging case studies, such as How to start decolonising your business, Power and empathy and How COVID-19 has changed university teaching ·        New ‘Additional Resources’ in each chapter This textbook is essential reading for anyone studying organizational behaviour at undergraduate or postgraduate level. A wealth of online resources for both students and lecturers, including a fully revised Instructor’s Manual, PowerPoint slides and additional case studies, are available via the companion website.  Stewart Clegg is Professor at the University of Stavanger, Norway; University of Sydney and Emeritus Professor at University of Technology Sydney, Australia Tyrone S. Pitsis is Professor of Strategy, Technology & Society at Durham University Business School. Matt Mount is Assistant Professor of Strategy and Innovation at Deakin Business School, Melbourne.